Cardiovascular Death Risk in Primary Central Nervous System Lymphoma Patients Treated With Chemotherapy: A Registry-Based Cohort Study - Guan, Tianwang; Qiu, Zicong; Su, Miao; Yang, Jinming; Tang, Yongshi; Jiang, Yanting; Yao, Dunchen; Lai, Yanxian; Li, Yanfang; Liu, Cheng (Frontiers in Oncology, 2021)
Abstract Purpose: The influence of chemotherapy on cardiovascular death (CVD) in patients with primary central nervous system lymphoma (PCNSL) is still ambiguous. We explored the impact of chemotherapy on CVD in PCNSL patients for assisting clinical decision-making. Methods: We obtained 2,020 PCNSL participants and 88,613 non-central nervous system lymphoma (NCNSL) participants with chemotherapy from Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2015. A 1:3 propensity score matching (PSM) was used to reduce the imbalance between PCNSL participants with chemotherapy and without chemotherapy, as well as the imbalance between PCNSL participants with chemotherapy and NCNSL participants with chemotherapy. Competing risks regressions were conducted to evaluate the independent influence of chemotherapy on CVD. Results: After 1:3 PSM, the CVD risk in PCNSL patients with chemotherapy was lower than both PCNSL patients without chemotherapy (decreased 53%) and NCNSL patients with chemotherapy (decreased 36%) (adjusted HR, 0.469 [95% CI, 0.255 - 0.862; P = 0.015]; adjusted HR in model 1, 0.636 [95% CI, 0.439 - 0.923; P = 0.017]). The CVD risk of chemotherapy decreased in PCNSL patients with age at diagnosis > 60 years old (adjusted HR, 0.390 [95% CI, 0.200 - 0.760; P = 0.006]), and those patients diagnosed at 2010-2015 (adjusted HR, 0.339 [95% CI, 0.118 - 0.970; P = 0.044]). Conclusion: PCNSL patients with chemotherapy are association with lower CVD risk. Our findings may provide new foundations that chemotherapy is the first-line treatment for PCNSL patients, according to a cardiovascular risk perspective.